2016
DOI: 10.1097/meg.0000000000000723
|View full text |Cite
|
Sign up to set email alerts
|

Clinical risk factors for delayed bleeding after endoscopic submucosal dissection for colorectal tumors in Japanese patients

Abstract: The presence of lesions in the rectum and three or more arterial bleeding occurrences during ESD were risk factors for post-ESD bleeding. Patients with these risk factors should be followed up carefully after ESD for colorectal epithelial neoplasms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
37
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 35 publications
3
37
1
1
Order By: Relevance
“…The report with the highest complication rate (12.0%) included subjects with mild bleeding that did not require endoscopic hemostasis (44). The rate of postoperative bleeding in other studies ranged from 0% to 12.0% (15,16,31,32,39-45), which was slightly higher than in the present study. The present study included patients who required endoscopic hemostasis.…”
Section: Discussioncontrasting
confidence: 84%
See 3 more Smart Citations
“…The report with the highest complication rate (12.0%) included subjects with mild bleeding that did not require endoscopic hemostasis (44). The rate of postoperative bleeding in other studies ranged from 0% to 12.0% (15,16,31,32,39-45), which was slightly higher than in the present study. The present study included patients who required endoscopic hemostasis.…”
Section: Discussioncontrasting
confidence: 84%
“…In this study, the perforation rate was almost equivalent to that in other reports (26-34,39-47). All cases with perforation in this study were treated conservatively with endoscopy, as previously reported in other institutes (26-32,36-49). …”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Since colorectal ESD is often complicated by delayed bleeding in 0.5-9.5% patients, it is important for endoscopists to determine when emergency endoscopy is necessary in order to treat this complication [1]. Although massive bleeding generally requires initial endoscopic hemostasis, most cases of bleeding do not require emergency repeat colonoscopy since bleeding usually spontaneously stops within several hours and does not recur prior to hospital discharge [2]. Nevertheless, no consensus exists regarding the safe and appropriate management of delayed bleeding following ESD.To address this question, Chiba et al [3] in the current issue of Digestive Diseases and Sciences reported a retrospective study assessing the feasibility of the "watch and wait" strategy, whereby clinicians based their decision to carry out emergency endoscopy on the basis of the patients' vital status and symptoms.…”
mentioning
confidence: 99%